PERILAKU EKONOMI RUMAH TANGGA PETANI LAHAN KERING DI KABUPATEN KARANGANYAR - Barokah, Umi; Masyhuri, Masyhuri; Waluyati, Lestari Rahayu; Hartono, Slamet (Jurnal Sosial Ekonomi Pertanian, 2015)
In 2012, the upland area in Karanganyar Districtreached 45.11% of agricultural land. The farmer problems are technical (erosion, soil fertility, water availability) and economic (fluctuation of production, pricing and income). They take off farm acivity in order to increase household income.The main objective of the study is to determine (1) farming cost andincome, (2) the diversity and contribution of off farm activity, (3) household income (4) consumption and investment of upland farm household.Based on altitude and proportion of upland area, the study was carried out in Jatiyoso. Respondent of 60 farmers was drawn randomly from Wonorejo village. The methods is descriptively analysis were applied to explain economic behavior of upland farm households. In average, the cost of upland farm is Rp 4.9120.720 and income Rp 13.716.773 in a year. Contribution of off farm activity (45,92%) more than upland farming (37,47%). Excess income are prioritized for investment to buy land and livestock. Food consumption from production itself reaches15,55 %. Non-food consumption especially to improve human quality in education and health. Keywords: farm household, income, off farm activity, up land